Have treatment protocols for primary CNS lymphoma advanced in the past 10 years?. Issue 10 (3rd October 2019) - Seidel, Sabine; Schlegel, Uwe
ABSTRACT: Introduction : Primary CNS lymphomas (PCNSL) are highly aggressive tumors and optimal treatment is not yet defined. For the last two decades, clinical trials have focused on developing efficient chemotherapy protocols with or without dose-reduced radiation to avoid late cognitive decline after whole brain radiotherapy (WBRT). Areas covered : This review addresses the question if these substantial developments have led to clinically relevant therapeutic improvement for PCNSL within the last decade. Expert opinion : The high risk of neurotoxic side effects of WBRT was further substantiated, and in most centers WBRT is omitted from first-line treatment in patients eligible for high-dose systemic methotrexate (HDMTX)-based chemotherapy. Intensified polychemotherapy regimens, particularly high-dose chemotherapy regimens with autologous stem cell transplantation (HD-ASCT), were investigated within prospective multicenter randomized trials and have achieved long-term disease control in a fraction of patients, but no significant progress was made for elderly patients, who are not able to tolerate intensified chemotherapy. Results on the efficacy of rituximab in PCNSL are conflicting; it did not show clinical benefit in a recent large prospective multicenter randomized trial. New substances such as immune-checkpoint inhibitors and targeted molecules are subject to investigation, but have not yet been implemented in clinical routine.